Enriched supervision to increase quality of early intensive behavioral intervention in autism: a pragmatic randomized controlled pilot study. Issue 1 (2nd January 2022) - Långh, Ulrika; Cauvet, Élodie; Perry, Adrienne; Eikeseth, Svein; Bölte, Sven
ABSTRACT: Methods to enhance the quality of delivered Early Intensive Behavioral Intervention (EIBI) for children with autism spectrum disorder (ASD) have received surprisingly little attention in previous research. In a pragmatic randomized controlled pilot study, we studied the feasibility and effects of enriched supervision (using detailed video feedback) on EIBI quality compared to regular supervision only, over a period of 4–6 months. EIBI was conducted in 30 children with ASD by preschool staff, where 18 received enriched, and 12 regular supervisions. EIBI quality was evaluated using the York Measure of Quality of Intensive Behavioural Intervention. The enriched supervision was deemed feasible and compared to staff receiving regular supervision. Preschool staff who received enriched supervision improved on overall quality of EIBI delivery, as well as specifically regarding goal-directedness, organization and efficiency of the EIBI. Findings support the significance of adequate education and supervision of EIBI providers for intervention quality assurance.